Two new species of Trichuris (Nematoda: Trichuridae) collected from endemic murines of Indonesia - Hasegawa, Hideo; Dewi, Kartika (Zootaxa, 2017)
Two new species of the genus Trichuris (Nematoda: Trichuridae) parasitic in the old endemic murids of Indonesia are described: T. musseri sp. nov. from Echiothrix centrosa (Murinae: Rattini) in Sulawesi and T. mallomyos sp. nov. from Mallomys rothschildi (Murinae: Hydromyini) in Papua Indonesia. Both species are characterized by having a gradually tapered and sharply pointed distal end of the spicule, being readily distinguished from most of the congeners known from murid rodents. Trichuris musseri is readily distinguished from T. mallomyos by having a much smaller body and large number of nuclei per subdivision of stichosome. The resemblance in spicule morphology between the two new species is of special interest because both hosts belong to different tribes and have different habitats and habits. It remains to be elucidated whether the resemblance is merely homoplasy or actually reflects close phylogenetic relationship of the parasites.